Do direito democrático: instituições jurídico-políticas e imaginário da democracia ateniense - Magdaleno, Rafael Tubone (2018)
The present paper intends to investigate the Athenian democracy. An idea that spread out and expanded to other pillars: its institutions, its imaginary, its Law. It seeks the specific status of this idea within the Greek civilizational panorama – especially the classical period, which is conventionally said to go from the 7th to the 4th century BCE – and to link this idea – a democratic one – to the juridical composition that supported it. The paper shows how it differs from our current legal structure and how binding the concepts of Law, of freedom and of democratic political regime were in that primeval time. This study is based on a literature review of democratic Athens, but also of interrelated notions, such as the history of democracy, Roman Law – which serves as a counterpoint to Athenian Law. Finally, we consider that Athenian democracy is not only structured just as direct democracy. It has institutions. It values freedom over the law; legal-political decisions take place within the Εκκλησία and may be reviewed; it presupposes a civic formation for public participation and generates a community linked to the notion of public word, in which the sophists are the "teachers" par excellence